The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1248/bpb.33.1522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combination Treatment with Dexamethasone and Mannitol on Neuronal Damage and Survival in Experimental Heat Stroke

Abstract: Unless immediately recognized and treated, heat stroke is often lethal, and victims who do survive may sustain permanent neurological damage.1) The clinical diagnosis of heat stroke is demonstrated when hyperthermia is accompanied with circulatory shock (arterial hypotension), intracranial hypertension, and cerebral ischemia and injury. 2,3) Meanwhile, the heat stroke-induced central nervous system dysfunction includes delirium, convulsion, or coma. 4) Hence, prolonging survival time in heat stroke victims may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 39 publications
(66 reference statements)
4
17
0
Order By: Relevance
“…During heat stroke, rodents display hyperthermia, arterial hypotension, intracranial hypertension, cerebral ischaemia, neuronal damage and overproduction of inflammatory cytokines [ 6 , 11 , 12 ]. The present results, as well as our previous results [ 3 , 4 , 13 ] revealed that all heat-stressed animals displayed systemic inflammation and activated coagulation, evidenced by increased TNF-α, IL-1β, PT, aPTT, and D-D dimer, and decreased IL-10 and protein C. Biochemical markers evidenced cellular ischemia and injury/dysfunction: plasma levels of BUN, creatinine, SGOT, SGPT, and ALP, and striatal levels of glycerol, glutamate, and lactate/pyruvate ratio, were all elevated during heat stroke. In contrast, the values of mean arterial pressure and striatal levels of local blood flow were all significantly lower during heat stroke.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…During heat stroke, rodents display hyperthermia, arterial hypotension, intracranial hypertension, cerebral ischaemia, neuronal damage and overproduction of inflammatory cytokines [ 6 , 11 , 12 ]. The present results, as well as our previous results [ 3 , 4 , 13 ] revealed that all heat-stressed animals displayed systemic inflammation and activated coagulation, evidenced by increased TNF-α, IL-1β, PT, aPTT, and D-D dimer, and decreased IL-10 and protein C. Biochemical markers evidenced cellular ischemia and injury/dysfunction: plasma levels of BUN, creatinine, SGOT, SGPT, and ALP, and striatal levels of glycerol, glutamate, and lactate/pyruvate ratio, were all elevated during heat stroke. In contrast, the values of mean arterial pressure and striatal levels of local blood flow were all significantly lower during heat stroke.…”
Section: Resultssupporting
confidence: 93%
“…After onset of heat stroke, rats revealed ischemia and injury in several cerebral regions, especially in the corpus striatum. Both of our previous [ 3 , 13 ] and present results displayed that the local CBF of striatum decreased significantly, but the values of striatal neuronal ischemic and injury index were sharply increased in rats with heat stroke (as shown in Figure 1 ). However, acute immediate treatment with DXM revealed appreciable decrements of neuronal damage, ischemic and hypoxic indexes in rats of heat stroke.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…To avoid the influence of diurnal cycling, heat exposure was started at approximately the same time each day between 9 and 10 a.m. Heat exposure was achieved by transferring the mice in their cage into a chamber (Jeio Tech, Daejeon, Korea) at 43°C and 60± 10% humidity for 15 min once a day. The heat condition was slightly modified from Yang et al, 14) based on survival rate. In preliminary test, mice with up to 15 min heat exposure at 43°C easily recovered in 10 min without death at room temperature.…”
Section: Methodsmentioning
confidence: 99%